Digital Pesantren Transformation Strategies Within The Modern Islamic Education Landscape: A Systematic Literature Review (SLR) 2021–2026 - Nofa Tria Rohana; Tri Wahyudi Ramdhan; Musohihul Hasan (AR-RASYID : Jurnal Pendidikan Agama Islam, 2026)
This study aims to formulate digital transformation strategies for pesantren in response to the challenges of Society 5.0 and to construct a conceptual framework for negotiating Islamic tradition (al-turath) with modern technology. The method employed is a Systematic Literature Review (SLR) following the PRISMA protocol, analyzing relevant scholarly articles from reputable databases published between 2021 and 2026. The results indicate that digital transformation in pesantren encompasses three primary aspects: pedagogical restructuring through network-based learning models, the adaptation of digital leadership by the Kyai, and the integration of Artificial Intelligence (AI) in disseminating religious teachings. However, significant challenges emerge, including the potential erosion of the authority of classical books (kitab kuning) and shifts in the socio-cultural values of